PENGARUH KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI DAN LINGKUNGAN KERJA SEBAGAI VARIABEL PEMODERASI (STUDI PADA PEGAWAI DIVISI SARANA PT. KERETA API INDONESIA (PERSERO) DAOP 8 SURABAYA - Affandy, Rizal Eka (Journal of Innovation in Business and Economics, 2016)
This study aimed to examine the effect of job characteristics on the performance, test the effect of motivation as a moderating variable job characteristics on the performance and test the effect of the work environment as moderating variable job characteristics on employee performance of PT Sarana Division. Kereta Api Indonesia (Persero) Daop 8 Surabaya. The sample used in this study is a random sample of 207 people. The results of the analysis Partial Least Square (PLS) this study shows that the job characteristics significant positive effect on employee performance, motivation positive effect was not significant to moderate the influence of job characteristics on the performance of employees, work environment positive effect was not significant to moderate the influence of job characteristics on the performance employee Divisi Sarana PT. Kereta Api Indonesia (Persero) Daop 8 Surabaya.  Keywords: job characteristics, motivation, work environment, employee performance.